Ajuste espacial e urbanização desigual: involução industrial e metropolização terciária em Belém - Tiago Veloso dos Santos (Confins)
The spread of urbanization throughout the Brazilian territory in the second half of 20th century was the defining process of Brazilian socio-spatial organization at the period. In Brazilian Amazon, the integration process that were vectors of regional urbanization, caused a spatial fix was directly affected one of its major cities, Belém, in which the social production of urban space occurred due to disruption of the pre-existing regional-urban industrial sector. Between the objectives of this paper highlighted the results of such loss, that has been resulting, in Belém, the absence of a industrial sector capable of guidind the urban-industrial accumulation as other Brazilian regions, thus making more and more dependent of economic organization bases in a tertiary sector of nascent metropolitan economy. In terms of methodological procedures, this research was developed in three m the moments: literature review about urban and regional economics, documental and iconographic survey of observed process and collections and organizations of quantitative data that dialogue with the proposed qualitative analysis.